Development of Infographic Geography Learning Media in Learning Material Class Xi in Senior High School State Purwodadi (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Learning media is one component of learning support. Learning media has the benefit of increasing student interest and creativity, besides that learning media also influences student learning interest. The media used should follow current developments in science and technology. This study aims to (1) produce infographic learning media, (2) determine the feasibility of infographic poster-based learning media. Making this infographic learning media uses the Borg & Gall development model which consists of ten manufacturing steps. Making this learning media using a supporting application, namely Canva. The development of this learning media produces a product, namely infographic media. Based on the results of the media development carried out, infographic media is suitable for use as a geography learning media based on; (a) The validation results of the material experts obtained a feasibility percentage of 73.66% with eligibility criteria, (b) The media expert validation results obtained a feasibility percentage of 92.72% with very feasible criteria, (c) The small group trial results obtained an eligibility percentage of 83, 30% with very feasible criteria (d) The results of the large group trial obtained an eligibility percentage of 82.65% with very feasible criteria. Based on the results of the validation of material and media experts as well as the results of trials on students, it can be concluded that infographic learning media is suitable for use as geography learning media.